Simulation of the production process of a mineral water industry by system dynamics method (Research, Society and Development, 2020)
This research was conducted with the objective of implementing a computer model to simulate the steps that comprise the operational flowchart of a mineral water industry, using the software Stella 8.0. The model defined as dynamic, stochastic and discrete consisted of eleven interconnected blocks. It was built following the steps of characterizing the real system, creating the conceptual model, structuring and verification of computational model, data collection, and model validation. From data collected in the real system we obtained fits of the distributions used in assembling and verifying the model. Validation of the program was conducted by comparing the data of the real system with simulated data. The values collected in the real system were within the upper and lower limits on the graph obtained by regression analysis, with a confidence level of 95%, ensuring that the computer model adequately represents the real system. However, the computational model developed is appliable to simulate the dynamics of processing lines of Mineral Water, being a tool of production control, which allows the visualization of the behavior of the real system, facilitates the identification of errors, improve production flow, and reduces manufacturing costs by controlling the total processing time.